(untitled) (Comparative & International Education Series, 2021)
In this chapter, we describe the development of a study abroad program at Texas Southern University (TSU) that started 20 years ago. Study abroad programs are one outlet to enhance internationalization at HBCUs by exposing minority students, specifically African Americans, to the history and culture of countries outside the United States. Pioneered in 1997, the study abroad program at TSU is co-sponsored with the University of Dar es Salaam, in Tanzania, East Africa. The success of this program created momentum among both faculty and students that led to a rapid expansion of international study opportunities on campus and the institutionalization of support for study abroad programs. The experience enriches the education at TSU, an urban HBCU institution, with an enrollment primarily of minority, nontraditional, commuter students. The overview may serve as a template or model for other HBCUs with similar demographics.